'Thrown into the fossil gap': Indigenous Australian ancestral bodily remains in the hands of early Darwinian anatomists, c. 1860–1916. (April 2022) - Turnbull, Paul
Abstract: This article examines in contextual depth the investigations of Indigenous Australian ancestral bodily remains by four influential British Darwinian comparative anatomists active between 1860 and 1919: George Rolleston (1829-1881), William Henry Flower (1831-1899), Alexander Macalister (1844-1919), and William Turner (1832-1916). It also reviews the examination of the structural morphology of the brains of four Indigenous Australians by Macalister's protégé, Wynfrid Lawrence Henry Duckworth (1870-1956). Since the 1970s, Darwinian scientists of the last third of the long nineteenth century have been represented in connection with the efforts of Indigenous Australian communities to have the remains of their ancestors returned for burial, as having acquired and investigated their skulls and other bodily structures to prove their evolutionary inferiority, and thereby legitimate their violent dispossession and near enslavement under so-called 'protective' regimes, where they struggled to maintain their families' health and well-being, their languages and culture. Racialized perceptions of Indigenous Australians as an evolutionarily primitive human type were perniciously influential among Australian-based and metropolitan British scientists, intellectuals, politicians and government officials during the last third of the long nineteenth century. However, as this article aims to show, by contextual scrutiny of the reportage of these leading four anatomists on their investigation of the skulls and brains of the first peoples of Tasmania and mainland Australia, they had no interest in proving Indigenous inferiority. They were driven by curiosity as to what investigation of the bodily remains of Indigenous Australians might disclose about the evolutionary genealogy of humankind. Hence, we would do well to see the outcomes of their investigations as having more complex connections with racialized perceptions of Australia's first peoples beyond medico-scientific circles, and the formulation of colonialist solutions for managing their future in the aftermath of dispossession by settler colonialism.